Chemically Stabilized DNA Barcodes for DNA‐Encoded Chemistry. Issue 36 (3rd August 2021) - Potowski, Marco; Kunig, Verena B. K.; Eberlein, Lukas; Vakalopoulos, Alexandros; Kast, Stefan M.; Brunschweiger, Andreas
Abstract: DNA‐encoded compound libraries are a widely used small molecule screening technology. One important aim in library design is the coverage of chemical space through structurally diverse molecules. Yet, the chemical reactivity of native DNA barcodes limits the toolbox of reactions for library design. Substituting the chemically vulnerable purines by 7‐deazaadenine, which exhibits tautomerization stability similar to natural adenine with respect to the formation of stable Watson–Crick pairs, yielded ligation‐competent, amplifiable, and readable DNA barcodes for encoded chemistry with enhanced stability against protic acid‐ and metal ion‐promoted depurination. The barcode stability allowed for straightforward translation of 16 exemplary reactions that included isocyanide multicomponent reactions, acid‐promoted Pictet–Spengler and Biginelli reactions, and metal‐promoted pyrazole syntheses on controlled pore glass‐coupled barcodes for diverse DEL design. The Boc protective group of reaction products offered a convenient handle for encoded compound purification. Abstract : DNA‐encoded compound libraries (DELs) are a widely used screening technology. DNA reactivity limits the reaction scope for library synthesis. Substituting the purines by 7‐deazaadenine yielded functional DNA barcodes with enhanced chemical stability. Controlled pore glass‐coupled barcodes tolerated isocyanide multicomponent reactions, the acid‐promoted Pictet–Spengler reaction, and Yb III ‐ and Au I ‐mediated pyrazole syntheses for DEL design.